PAEDIATRIC THORACIC TUMOUR RESECTION: CHALLENGE FOR AN ANAESTHESIOLOGIST - Ahmed, Syed Shabbir; Samad, Khalid; Yousuf, Muhammad Saad; Junejo, Faisal (Journal of Ayub Medical College Abbottabad, 2020)
Paediatric thoracic tumours resection is one of the most difficult procedure for any anaesthetist. Paediatric population is different from adults in many aspects, as they have small thoracic volume and more compressible mass effect on their airway and vascular structures. we are reporting a case of a huge paediatric thoracic tumour resection occupying the left thoracic cavity. The possible mechanism, consequences, prevention and management discussed in this report. Keywords: mediastinal mass; paediatric thoracic surgery; teratoma